Resting energy expenditure and kidney disease: a narrative review - Li, Zhuoxing; Zhang, Sunhan; Xiao, Xiang; Sun, Yun (Frontiers in Nutrition, 2025)
ObjectivesTo explore the complex relationship between resting energy expenditure (REE) and kidney disease, and to synthesize evidence on REE assessment methods, influencing factors, and clinical implications for medical nutrition therapy (MNT).BackgroundPatients with kidney disease exhibit significant variations in metabolism and energy expenditure, increasing risks of comorbidities and adverse events. Accurate REE assessment is critical for precise energy intake planning and individualized MNT. However, current REE evaluation methods show inconsistencies, and factors driving REE changes (e.g., renal function, inflammation, comorbidities, medications) lack comprehensive analysis.ResultsSignificant discrepancies were identified across methodologies for assessing REE in kidney disease populations. Multiple disease-related factors—including renal function decline, inflammatory status, comorbidities, and pharmacotherapy—were found to dynamically alter REE patterns. While existing predictive equations offer clinical utility, they demonstrate notable limitations in applicability across diverse patient subgroups. Critically, addressing REE within personalized MNT significantly improves prognostic outcomes in this population.ConclusionThis review consolidates advances in REE-kidney disease research, establishes standardized assessment frameworks, and validates REE’s role in prognosis-focused MNT. It provides guidance for future studies and clinical practice, emphasizing REE optimization as essential for improving nutritional interventions in nephrology.